Aggregate-based sub-CMC solubilization of hexadecane by surfactants1. Issue 95 (15th October 2015) - Zhong, Hua; Yang, Lei; Zeng, Guangming; Brusseau, Mark L.; Wang, Yake; Li, Yang; Liu, Zhifeng; Yuan, Xingzhong; Tan, Fei
<x xml:space="preserve">Abstract</x> SDBS or Triton X-100 at sub-CMC concentrations enhances hexadecane solubilization due to the aggregate formation mechanism. The sub-CMC aggregate size decreases with increasing surface excess of the surfactant.